Thermal analysis of kenaf sandwich panel - Johari, Norhasnidawani; Hassan, Noor Azlina; Halim, Zahurin (Trans Tech Publications, Switzerland, 2013)
The introduction of the eco-core sandwich panel composite is contributing a new approach to the designer to achieve high performance and light weight. In this research project, the new kenaf eco-core sandwich panel will be developed and then laminated with galvanized steel. The final goal is to find the optimum eco-core metal matrix composite sandwich structure with maximum mechanical properties such as stiffness and buckling. Kenaf eco-core sandwich will be fabricated and study on the interaction between eco-core sandwich panel and metal faces will be performed. The characterization of the eco-core sandwich panel will be done using different analytical tools. This study would provide a way to enhance the application of this new eco-core metal matrix composite sandwich structure. The amount of sample used was approximately 12 mg. The temperature profile was from 27°C to 1000°C at a heating rate of 10°C/min. In this study, result shows that degradation of composites starts to occur at about 180°C. Increasing the kenaf percent ratio will decrease the percent residue.